Plant-Based Milks: Rice - Meagan Lamothe; Daniela Rivero-Mendoza; Wendy Dahl (EDIS)
Rice milk is a plant-based, nondairy beverage made primarily from milled rice and water. It is marketed as an allergy-friendly, easy-to-digest, vegan substitute for cow's milk. Similar to other plant-based beverages, rice milk usually has an opaque white or beige color and creamy texture resembling that of cow's milk. This new 4-page publication of the UF/IFAS Food Science and Human Nutrition Department describes how rice milk is made, its ingredients and nutrient profile, and potential health benefits and risks of consumption. Written by Meagan Lamothe, Daniela Rivero-Mendoza, and Wendy J. Dahl. https://edis.ifas.ufl.edu/fs412